Digital engagement strategies and tactics in social media marketing. (6th March 2020) - Drummond, Conor; O'Toole, Thomas; McGrath, Helen
Abstract : Purpose: Digitalisation has increased the importance of online forms of marketing, including social media (SM) marketing, for entrepreneurial firms. This paper aims to identify digital engagement strategies and tactics in developing SM marketing capability. Design/methodology/approach: The study uses ethnographic content analysis of an entrepreneurial firm and a network of business-to-business (B2B) actors to classify 1, 248 B2B Facebook posts and Twitter tweets from a case of an artisan food producer in addition to semi-structured interviews with 26 networked actors. Findings: The authors derive a range of digital engagement strategies (8 in total) and tactics (15 in total) for the four defining layers of SM marketing capability, namely, connect, engage, co-ordinate and collaborate. Research limitations/implications: This research focuses on a case study and a network of B2B actors within the artisan food sector. However, the strategies and tactics are applicable to other entrepreneurial firms and contexts. Practical implications: The digital engagement strategies and tactics are of direct practical benefit to entrepreneurial firms willing to learn and develop SM marketing capability in interaction with their B2B partners. Originality/value: This study investigates three under-researched areas, SM as it relates to B2B relationships, and entrepreneurship, and marketing capability gaps in an era of rapid digitalisation. The definition of SM marketing capability and associated digital engagement strategies and tactics are new to the extant literature moving forward the understanding of SM B2B marketing in theory and practice.